The Impact of School Climate on Well-Being Experience and School Engagement: A Study With High-School Students - Lombardi, Elisabetta; Traficante, Daniela; Bettoni, Roberta; Offredi, Ilaria; Giorgetti, Marisa; Vernice, Mirta (Frontiers in Psychology, 2019)
The aim of this work is to contribute to the identification of the factors which can promote students’ engagement at school and support flourishing in young people. According to the Positive Education (Seligman, 2011), there is a strong relationship between school environment and student’s well-being. Fatou and Kubiszewski (2018) found that the quality of the school climate perceived by the students influences engagement in school activities. In this study, 153 students (M = 67) attending 10th grade were presented with tests and questionnaires to assess individual assets (personality traits, literacy skills), emerging appraisals (school-climate, well-being experience) and emerging actions (school engagement), according to the Student Well-Being Model proposed by Soutter et al., (2014). Path analysis showed that the best model includes neither individual assets nor direct effect of school climate on engagement, as the effect of school climate on engagement is mediated by well-being experience. In other words, school climate has been confirmed as an important factor to be considered to improve engagement in school activities, but it is effective only when its influence can modify the well-being experience of the students. These results support the perspective of Positive Education, as intervention on school environment is expected to exert positive effects not only on students’ well-being, but also on their engagement in school activities and learning, irrespective to students’ assets. Therefore, improving school climate means to support well-being experience and to reduce dropout risk also in students with learning difficulties and with personality traits, which might lead to dysfunctional behaviors. This work encourages working in/with schools to implement positive education programs that support and sustain a positive school climate and culture for school-community well-being.